A RARE CAUSE OF PNEUMOPERITONEUM: PERFORATED APPENDICITIS - Şahin, Serdar; Cavusoglu, Turgut; Kubat, Mehmet; Calis, Hasan (Journal of Ayub Medical College Abbottabad, 2016)
Peptic ulcer perforation is the most common cause of pneumoperitoneum (75%). The rate of the perforation of acute appendicitis is 20-30% and the rate of its co-occurrence with pneumoperitoneum is 0-7%. In this report, a patient with sub-diaphragmatic free air due to perforated appendicitis. Keywords: Pneumoperitoneum, Perforated appendicitis